Criação e sublimação: uma leitura inspirada em Freud e Ricoeur da obra de Proust Em Busca do Tempo Perdido - Souza, Talitha Ferraz de (2007)
As a reflection on the creation in art, especially in literature, starting from the psychoanalitic concept of sublimation, this thesis presents for consideration the reading of Proust's work: In Search of Lost Time, aiming on the elucidation of this process of creation. The concept of sublimation, although subject to multiple readings, allows the comprehension of the creation in art as a process of "flexibilization" in relation to compulsive originary fixations, that can be understood in Proust's work as a "search of lost time" making possible through a "re-encountered time its literary writing